Ashwagandha (Withania somnifera) Reverses β-Amyloid1-42 Induced Toxicity in Human Neuronal Cells: Implications in HIV-Associated Neurocognitive Disorders (HAND) - Kurapati, Kesava Rao Venkata; Atluri, Venkata Subba Rao; Samikkannu, Thangavel; Nair, Madhavan P. N. (PLOS ONE, 2013)
Alzheimer’s disease (AD) is characterized by progressive dysfunction of memory and higher cognitive functions with abnormal accumulation of extracellular amyloid plaques and intracellular neurofibrillary tangles throughout cortical and limbic brain regions. At present no curative treatment is available, and research focuses on drugs for slowing disease progression or providing prophylaxis. Withania somnifera (WS) also known as ‘ashwagandha’ is used widely in Ayurvedic medicine as a nerve tonic and memory enhancer. However, there is a paucity of data on the potential neuroprotective effects of W.somnifera against β-Amyloid (1–42)-induced neuropathogenesis. In the present study, we have tested the neuroprotective effects of methanol:Chloroform (3:1) extract of ashwagandha against β-amyloid induced toxicity and HIV-1Ba-L (clade B) infection using a human neuronal SK-N-MC cell line. Our results showed that β-amyloid induced cytotoxic effects in SK-N-MC cells as shown by decreased cell growth when tested individually. Also, confocal microscopic analysis showed decreased spine density, loss of spines and decreased dendrite diameter, total dendrite and spine area in clade B infected SK-N-MC cells compared to uninfected cells. However, when ashwagandha was added to β-amyloid treated and HIV-1 infected samples, the toxic effects were neutralized. Further, the MTT cell viability assays and the peroxisome proliferator-activated receptor-γ (PPARγ) levels supported these observations indicating the neuroprotective effect of WS root extract against β-amyloid and HIV-1Ba-L (clade B) induced neuro-pathogenesis.